A STUDY ON THE REGISTER OF POLITY - Nugroho, Radityo Tri; Sari, Afifah Linda (English Department of Faculty of Tarbiyah and Teacher Training, 2019)
The language of Indonesian politics is quite interesting. There are many phenomena of language abuse such as language manipulation and meaning reduction, which often occur. This research is meant to find 1) the form of the polity register, 2) the kinds of meaning polity register and 3) the characteristics of the polity register. Dealing with the research method, the writer applies qualitative method. The writer takes the data from the Indonesian newspaper ?Suara Merdeka? which contains register polity. She collects the data by reading, scrutinizing, and listing them. To analyze the data, the writer uses semantic analysis based on Poedjosoedarmo theory to determine the changing meaning of the register. Having analyzed the data, the writer finds two forms of polity register namely: word and phrase. The words are in the form of simple word (26, 7%), compound word (26, 7%), and complex word (24, 4%), abbreviation and blended, each has 2,2%. In the form of phrase (17, 8%) Related to the meaning, the writer finds five kinds of changing meaning, namely: narrower than the real meaning (8, 9%), share some features whereas each of them has different meaning (24, 5%), identical to the real meaning (13,3%), and different from the real meaning (53,3%). Meanwhile, the Language styles of Indonesian polity register are euphemism (57,7%), metaphor (6,7%), hyperbola (13,3%), and metonymy (22,2%). The result of this research shows that the biggest amount of the register meaning of the Indonesian polity is different from the real meaning and tends to be euphemism. Those phenomena indicate that the polity register used by Indonesian politician tends to hide the real meaning. These may happen since there are some interests behind the Indonesian polity register, among others are to maintain and to retain power. In sum, the register is used to keep the authority goes on.